Test of Ecogeographical Rules on Sparrows (Passer spp.) along the Elevation Gradient of the Himalaya in Central Nepal - Deepa Dangol; Laxman Khanal; Naresh Pandey; Anuj Ghimire; Randall C. Kyes (Ecologies, 2022)
Animals inhabiting colder climates have a larger body size (Bergmann’s rule) and smaller body extremities (Allen’s rule), which help homeothermic animals to retain heat. Such ecogeographical phenomena have frequently been observed in animals along the latitudinal gradient and have occasionally been tested along the elevational gradient. This study tested whether these ecogeographic rules hold true for the morphology of sparrows (Passer spp.) along the elevational gradient offered by the Himalaya in central Nepal. Seventy house sparrows and twenty-eight tree sparrows were captured from 22 different localities of central Nepal between 100 and 3400 m asl, and morphological traits such as body size (body mass, tarsus length, wing length and tail length) and body extremities (bill length and bill width) were measured. Linear regression analysis was used to test the association of morphological measurements with elevation and climatic variables. House sparrows (Passer domesticus) had a wider elevational distribution range and exhibited significantly larger body sizes than the Eurasian tree sparrows (P. montanus). House sparrows had larger body sizes and smaller bills at higher elevations in adherence to Bergmann’s rule and Allen’s rule. Bill length in house sparrows showed a positive association with the temperature following the proposition of Allen’s rule. However, the morphological measurements in Eurasian tree sparrows did not show a distinct pattern with elevation and climatic variables. Therefore, this study concludes that ecogeographical phenomena such as Bergmann’s rule and Allen’s rule could be species-specific based on their biological and ecological characteristics.